FACTORS RELATED TO EXCLUSIVE BREAST FEEDING TO MOTHERS WHO HAVE BABIES IN THE WORKING AREA OF SEMERAP PUBLIC HEALTH CENTER KERINCI DISTRICT 2022 - M. Taufik Akbar; M. Ridwan; Puspita Sari (International Journal Of Health Science, 2023)
The type of research used is cross-sectoral research, research conducted over a long period of time where this study is designed to study the correlation between exposure and consequences or effects at the same time. The sample size in this study is 65 people, the technique used in sampling is This study uses simple random sampling, which is a technique that has the same opportunity according to the proportion (regardless of the size of the population) in sampling. This study found that there is a relationship between knowledge, attitude and support of health workers towards exclusive breastfeeding for mothers who have babies and there is no relationship between exposure to information media and culture towards exclusive breastfeeding for mothers who have babies, P-Value knowledge < 0.05 (0.002), Attitude P-Value < 0.05 (0.028), statistical health worker support (P-Value=0.019), The factors related to exclusive breastfeeding are knowledge, attitudes and health workers and there is no relationship between exposure to information media and culture.